Evaluation of cardiac function in patients with liver cirrhosis using tissue Doppler study - Mohammed M Ashmawy; Hosny A Younis; Mahmoud A Abd Elbaset; Haitham A Abdel Rahman; Ahmed M Ashmawy; Muhammad A Shawky; Mohammed M Abd Elnasser (SpringerOpen, 2018)
Background and aim Cardiac dysfunction is a prevalent finding in patients with liver cirrhosis. We aimed to evaluate left ventricular function by tissue Doppler imaging in patients with liver cirrhosis. Patients and methods This is a cross-sectional case-control study that involved 90 patients with liver cirrhosis: 30 patients with Child A, 30 patients with Child B, and 30 patients with Child C cirrhosis. Moreover, 45 healthy volunteers were included in the study as a control group. All patients and controls were examined by conventional Doppler and tissue Doppler echocardiography. Results Patients with liver cirrhosis showed significantly lower ejection fraction (EF) levels than control group (P=0.001), but only nine patients showed EF levels less than 55. Moreover, there is significantly decrease in EF in patients with decompensated cirrhosis than those with compensated cirrhosis (P=0.005). A total of 60 patients showed diastolic dysfunction: 10 patients with Child A, 20 patients with Child B, and 30 patients with Child C cirrhosis. There were significantly differences between patients with liver cirrhosis and control group in the other parameters of systolic (S wave and myocardia performance index) and diastolic (early and late velocity and deceleration and isovolumetric relaxation time) functions. Conclusion Patients with liver cirrhosis showed significantly decreased left ventricular systolic and diastolic functions than control group, which is more pronounced in decompensated than compensated patients.